Further Evaluation of Rizatriptan in Menstrual Migraine: Retrospective Analysis of Long-term Data - Silberstein, Stephen D.; Massiou, Helene; McCarroll, Kathleen A.; Lines, Christopher R. (Headache, 2002)
Objective.—To determine the long‐term efficacy of oral rizatriptan 10‐mg wafers in the treatment of menstrual migraine attacks. Methods.—Data from an extension study where patients with migraine used rizatriptan 10 mg to treat moderate or severe migraine attacks occurring over periods of up to 6 months were included in a retrospective analysis. Patients used a diary card to record details of each migraine attack and onset of menstruation. Attacks in women were classified as menstrual or nonmenstrual according to 3 time windows relative to onset of menstruation (day 0): −3 to +3 days (7‐day window), −2 to + 2 days (5‐day window), and 0 to +1 days (2‐day window). The analysis looked at the efficacy of rizatriptan 10 mg by menstrual category of attack for each definition on three measures: pain relief at 2 hours (reduction of pain to mild or none), pain free at 2 hours, 24‐hours sustained pain free (pain free at 2 hours with no headache recurrence and no use of additional medications from 2 to 24 hours). Results.—Ninety‐five women used rizatriptan 10 mg to treat a total of 1,839 attacks. The percentage of menstrual attacks was 30% for the –3 to +3 days definition, 23% for the −2 to +2 days definition, and 11% for the 0 to +1 days definition. Rizatriptan 10 mg was equally effective in menstrual and nonmenstrual migraine attacks regardless of the definition used. For example, using the −3 to +3 days definition, 78% of menstrual migraine attacks were relieved at 2 hours after dosing compared with 78% of nonmenstrual attacks. Pain relief rates for the other definitions were as follows: −2 to +2 days, menstrual  =  78%, nonmenstrual  =  78%; 0 to +1 days, menstrual  =  79%, and nonmenstrual  =  78%. No differences between menstrual and nonmenstrual attacks were found for the 2‐hour pain free and 24‐hour sustained pain free measures for any of the three definitions. Conclusion.—Rizatriptan 10‐mg wafers were equally effective in the treatment of menstrual and nonmenstrual migraine attacks occurring over 6 months, regardless of the precise definition of menstrual association used and even when the outcome criteria were very stringent. These data provide further evidence that triptans are effective treatments for menstrual migraine.